2003
DOI: 10.1677/joe.0.1790107
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin at low doses stimulates pituitary GH whereas it decreases IGF-I and IGF-binding protein-3 in rats

Abstract: While it is well known that sepsis inhibits serum IGF-I and its gene expression in the liver, the effect on pituitary GH and IGF-binding protein-3 (IGFBP-3) is poorly understood. The GH-IGF-I-IGFBP-3 response to different doses of lipopolysaccharide (LPS) administration has been investigated in adult male rats. Two experiments were performed, administration of low doses of LPS (5, 10, 50 and 100 µg/kg) and high doses of LPS (100, 250, 500 and 1000 µg/kg). Rats received two i.p. injections of LPS (at 1730 h and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
2
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 42 publications
6
32
2
7
Order By: Relevance
“…In addition, cytokines and LPS are able to inhibit GHR and IGF-I gene expression both in vitro and in vivo (Wof et al 1996, Defalque et al 1999, suggesting that LPS induces GH resistance. Furthermore, LPS, at low doses, decreases liver IGF-I and IGFBP-3 gene expression in rats, whereas it stimulates GH secretion (Priego et al 2003b). All these data indicate that one of the mechanisms by which LPS injection inhibits hepatic GHR, IGF-I and IGFBP-3 gene expression is by acting directly on the liver.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, cytokines and LPS are able to inhibit GHR and IGF-I gene expression both in vitro and in vivo (Wof et al 1996, Defalque et al 1999, suggesting that LPS induces GH resistance. Furthermore, LPS, at low doses, decreases liver IGF-I and IGFBP-3 gene expression in rats, whereas it stimulates GH secretion (Priego et al 2003b). All these data indicate that one of the mechanisms by which LPS injection inhibits hepatic GHR, IGF-I and IGFBP-3 gene expression is by acting directly on the liver.…”
Section: Discussionmentioning
confidence: 81%
“…LPS-induced decrease in serum concentrations of IGF-I and IGFBP-3 is due to a direct inhibitory effect of LPS on liver IGF-I and IGFBP-3 gene expression, regardless of pituitary GH secretion (Defalque et al 1999, Priego et al 2003b. Induction of inducible nitric oxide synthase (iNOS) during sepsis is involved in the inhibition of IGF-I-IGFBP-3 after LPS administration (Priego et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…IGFBP3 concentration was determined in total rat serum by Western blot analysis 38 developed with 125 I-labelled rat IGF-I (DSL) Oligo sequences, annealing temperatures (Tm) and elongation times at 721C are indicated. GADPH GATGGTGAAGGTCGGTGTG CTTCCACGATGCCAAAGTTG 3 68 87 IGF-I TTCAGTTCGTGTGTGGACCAAGG GAAGTCCCAGCCCCTATCGACAC 2 63 87 IGFBP3 CCTCCGAGTCTAAGCGGGAGAC GCATTGCCTCAGCGTGCAGAG 2 63 86 HGF AGGGAATCCTCTCGTTCCTTGG GAGGCGAGGCGAAACGCAAAC 3 62 83 Abbreviations: GADPH, glyceraldehyde-3-phosphate dehydrogenase; HGF, hepatocyte growth factor; IGF-I, insulin-like growth factor-I; IGFBP3, IGF-binding protein 3; PCR, polymerase chain reaction.…”
Section: Serum Analytical Methodsmentioning
confidence: 99%
“…Forty rats were injected intraperitoneally with LPS (250 µg/kg) or saline at 1800 h on one day and at 1000 h on the following day. Rats were killed by decapitation 3 h after the second LPS or saline injection, between 1300 h and 1345 h. This LPS administration protocol has been shown to decrease levels of serum IGF-I and its mRNA in the liver (Priego et al 2003a). In order to study if glucocorticoid administration is able to prevent the effect of LPS on IGF-I, rats were pretreated with dexamethasone.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…LPS administration decreases circulating levels of IGF-I both in humans and in experimental animals (Fan et al 1994, Soto et al 1998. We have previously observed that the decrease in serum IGF-I is associated with a decrease in growth hormone (GH) receptor and IGF-I synthesis in the liver (Priego et al 2002a(Priego et al , 2003a.…”
Section: Introductionmentioning
confidence: 99%